209k views
0 votes
Anjeli writes the equation (a+b)2=c2+4(12ab) to begin a proof of the Pythagorean theorem.

Use the drop-down menus to explain why this is a true equation.

Anjeli writes the equation (a+b)2=c2+4(12ab) to begin a proof of the Pythagorean theorem-example-1

1 Answer

2 votes

Answer:

Therefore Anjeli is correct and


(a+b)^(2)=c^(2)+4((1)/(2)ab) is TRUE.

Explanation:

Given:

Label on triangle as ΔABC right angle at C such that

AB = c .....(Hypotenuse)

AC = b ....(Longer leg)

BC = a ....(Shorter leg)

To Prove:


(a+b)^(2)=c^(2)+4((1)/(2)ab)

Proof:

We know, in Right angle triangle ABC by Pythagoras theorem we get,


(\textrm{Hypotenuse})^(2) = (\textrm{Shorter leg})^(2)+(\textrm{Longer leg})^(2)

Substituting the values we get


AB^(2)=BC^(2)+AC^(2)\\\\c^(2)=a^(2)+b^(2) ...............( 1 )

Now the Left hand side of what Anjeli wrote is

Left hand side = (a+b)²

Using identity (A+B)² = A²+ B² + 2AB we get

Left hand side = a²+ b² + 2ab

From ( 1 ) we have
c^(2)=a^(2)+b^(2)

Substituting we get

Left hand side = c² + 2ab ...........................( 2 )

Now,

Right hand side =
c^(2)+4((1)/(2)ab)

Dividing 4 by 2 we get 2, hence

Right hand side =
c^(2)+2ab
.........................( 3 )

Therefore,

Left hand side = Right hand side From ( 2 ) and ( 3 )


(a+b)^(2)=c^(2)+4((1)/(2)ab) ..True

Therefore Anjeli is correct and


(a+b)^(2)=c^(2)+4((1)/(2)ab) is TRUE.

Anjeli writes the equation (a+b)2=c2+4(12ab) to begin a proof of the Pythagorean theorem-example-1
User Freddygv
by
4.8k points